E-cigarette Smoking (Vaping) and Markers of Vascular Wall Damage in Young Subjects without Cardiovascular Disease - V. I. Podzolkov; A. E. Bragina; N. A. Druzhinina; L. N. Mohammadi (Столичная издательская компания, 2021)
Aim: to investigate the effect of nicotine-containing vapes in comparison with traditional tobacco smoking on markers of vascular wall damage: high sensitivity C-reactive protein (hsCRP), albuminuria (AU), and ankle-brachial index (ABI).Material and Methods: We examined 369 young subjects without cardiovascular diseases (age median 21 [20;21] years) (159 men and 210 women). The hsCRP levels in the serum were assessed by immunochromatographic express method. AU was investigated in daily urine by a quantitative reflex photometry. ABI was determined by plethysmography.Results: All subjects were divided into groups: non-smokers (n=196, 53.1%), smokers of traditional cigarettes (n=83, 22.5%) and smokers of nicotine-containing vapes (n=90, 24.4%). The groups did not differ in main anthropometric data. Median hsCRP levels in smokers (14.30 [11; 16.5] mg/l in tobacco-smokers and 13.15 [9.65; 17.5] mg/l in vapers) were significantly higher vs nonsmokers (3.0 [2; 5.6] mg/l). In tobacco-smokers (33.0  [21.5;  60]  mg)  and  vape  smokers  (45.0  [20;  115]  mg),  the  median  AU  was  statistically  significantly  higher  than  in  non-smokers  (12.0 [10; 20] mg). ABI levels were significantly lower in the groups of tobacco smokers (0.98 [0.91; 0.99]) and vapers (0.85 [0.79; 0.93]) when compared with nonsmokers (1.125 [1.01; 1.18]), and the median ABI in vapers was lower than in tobacco smokers (p<0.001). In the group of tobacco smokers, the hsCRP level correlated with the smoker's index (rs=0.31, p<0.05), and AU (rs=0.54, p<0.05) and ABI (rs=-0.28, p<0.05) with a daily inhaled nicotine dose. In the group of vapers, CRP was associated with smoking experience (rs=0.338, p<0.05), AU with a daily inhaled nicotine dose (rs=0.79,  p<0.05), and  ABI with  BMI (rs=-0.33,  p<0.05), heart  rate (rs=-0.24,  p<0.05) and  smoking experience  (rs=-0.235, p<0.05). According to the results of multivariate regression analysis the hsCRP level was related with only the smoking experience (B=0.91±0.19, p=0.000005), AU level with the daily inhaled nicotine dose (B=1.59±0.7, p=0.0121) and smoking experience (B=3.07±1.23, p=0.0179), and ABI level with only smoking experience (B=-0.09±0.004, p=0.0419).Conclusion: In smokers, both traditional and vapers, the levels of hsCRP, AU are significantly higher, and the ABI is lower than in healthy young nonsmokers. The most significant influence on the level of hsCRP is exerted by the experience of  tobacco  and  vape  smoking;  to  the  AU  level  - the experience of tobacco and vaping and the daily inhaled nicotine dose, and by the value of the ABI - the experience of vaping.